Tubo-ovarian abscess with sepsis in a nonagenarian woman: a case report and literature review - Kuan-Yi Chen; Jen-Yu Tseng; Chih-Yu Yang (BMC, 2019)
Abstract Background A complete infectious focus survey relies on a thorough physical examination as well as a pelvic examination. Tubo-ovarian abscess, though less likely to occur in senior women, may become a life-threatening disease requiring emergent surgery. Hence, clinical awareness and aggressive management are warranted to avoid delayed diagnosis and subsequent complications. Case presentation We report a post-menopausal woman presented with sepsis of unknown origin, which turned out to be a huge tubo-ovarian abscess. Although tubo-ovarian abscess mostly occurs in women of fertile age, it is likely that the immune status of our post-menopausal patient was compromised because of old age and uremia. Moreover, due to underlying dementia, she could not express her discomfort in the early stage. Her sepsis resolved after a unilateral salpingo-oophorectomy surgery and antibiotic treatment. It is crucial to exclude pelvic inflammatory disease (PID) if no specific source of infection can be identified. Conclusions Rupture of the tubo-ovarian abscess is a condition of high mortality rate. Although tubo-ovarian abscess is more likely to develop in patients aged 15-25 years old, the tubo-ovarian abscess should be listed as a differential diagnosis in all post-menopausal women, especially those who are immunocompromised or with a palpable pelvic mass, to enable timely management and better prognosis.